Congenital malformation of liver in a West African dwarf goat - Ikpegbu, E; Nlebedum, UC; Nnadozie, O (Bangladesh Veterinarian, 2013)
Abstract not available DOI: http://dx.doi.org/10.3329/bvet.v30i1.16284 Bangl. vet. 2013. Vol. 30, No. 1, 39-40